A model of KPI for measuring ICT service quality - Nor, Rozi Nor Haizan; Alias, Rose Alinda; Abdul Rahman, Azizah (Departemen Sistem Informasi, Institut Teknologi Sepuluh Nopember, 2013)
This paper proposes a model to develop key performance indicators (KPIs)for the purpose of measuring ICT service quality (ICTSQ). In this decade,the importance of ICT in every stage of work by individuals, businesses or organizations are very apparent and cannot be denied. Hence, ICT services(ICTS) have become critical activities that need to be measured from time totime to ensure the quality and advantages of the ICT usage. It has been proven since many research works in service quality areas, including ICTS, have discussed the assessment, measurement and improvement of their service quality by proposing related models or frameworks. However, there is still a lack of provision a quantifiable approach by which to measure the ICTSQ since most of the previous research were only focused on the initial stage of service quality assessment and measurement. Thus far, the majority of them only had concerns regarding analyzing and identifying various factors and attributes of service quality based on the particular context involved. Due to this problem, it has come to the attention of this study to develop relevance KPIs for measuring ICTSQ. This paper proposes the development of KPI as a quality measurement approach for ICT services(ICTS). KPI is suggested as being the latest and most effective measureable approach for assessing performance in many aspects and contexts, including the aspect of ICTS. For measuring purposes, this study reviewed the current ICTS scope and ICTSQ factors based on the context involved. The investigation is done within the context of Malaysian Universities (MUs). Interviews to ICTS stakeholders were conducted within the context to get the empirical data. The KPI development model is intended to provide ideas and guidelines for the purpose of ICTSQ measurement for ICTSQ measurement.